Polycystic Ovarian Syndrome: An Uncommonly Known Plight - Tayyaba Ahmed (KARACHI MEDICAL AND DENTAL COLLEGE, 2020)
Through this respected journal, I would like to bring the attention of the readers towards the level of awareness of Polycystic Ovarian Syndrome (PCOS) among the general public in Karachi. PCOS is a common endocrine disorder among women of reproductive age, diagnosed by the presence of menstrual irregularity, hyperandrogenemia, and multiple cysts in the ovary that is visualized on transvaginal ultrasound1